Dietary omega-3 fatty acids affect the growth performance of broiler chickens reared at high stocking density - Shahgol Rahbari; Abdolreza Salehi; Seyed Davood Sharifi; Shirin Honarbakhsh (Poultry Science)
The present study was conducted to investigate the effects of dietary omega-3 fatty acids in broiler chickens exposed to high stocking density (SD) on growth performance, carcass characteristics, breast meat quality, blood biochemical indices, nutrient digestibility and litter quality. A total of 420 one-day-old broilers were used in 2 × 2 factorial arrangements with 2 levels of SD (low: 9 birds/ m2 and high: 17 birds/ m2) and 2 levels of omega-3 fatty acids (low and high omega-3; 0.057 and 0.5% of the diet, respectively) in a completely randomized design with 5 replicates for each treatment. Live body weight (LBW), feed intake (FI), and feed conversion ratio (FCR) were recorded periodically. The apparent metabolizable energy (AME), digestibility of crude protein (CP), organic matter (OM), and lipid of experimental diets, were measured from days 30 to 37 of age. The results showed that body weight gain (BWG) and FCR was improved (P < 0.05) in high SD broilers during the grower phase (days 15–24).The BWG of broilers under high SD and dietary omega-3 fatty acids was higher than others (P < 0.05) during the finisher phase (d 25-40). Carcass and total heart weight were higher in birds fed diets containing omega-3 fatty acids under high SD than in birds fed a diet low in omega-3 fatty acids at low or high SD (P < 0.05). The serum concentration of cholesterol in broilers with high SD fed diets high in omega-3 fatty acids was lower than broilers with high SD fed diets low in omega-3 fatty acids (P < 0.05). High SD decreased AME and CP digestibility (P < 0.05). Dietary omega-3 fatty acids, increased AME and digestibility of OM and lipid (P < 0.05). In broiler chickens raised at low stocking density, feeding a high-omega-3 diet reduced litter nitrogen levels compared to feeding a low omega-3 diet (P < 0.05). In summary, omega-3 fatty acid may have the potential to reduce negative effects of high SD on broiler production by enhancing the nutrient digestibility and litter quality.